032 Genomic prediction accuracies using regularized quantile regression (RQR) methodology. (1st March 2017) - Barroso, L. M.; Morgante, F.; Mackay, T. F.; Nascimento, A. C. C.; Nascimento, M.; Serão, N. V.
Abstract: The objective of this work was to evaluate the use of regularized quantile regression (RQR) for genomic prediction analyses in traits with or without skewness and with different proportions of epistatic variance. Data were simulated for 2500 individuals. The genome included 5K markers and 50 QTL for a lowly heritable trait (heritability = 0.1) simulated for six scenarios: combinations of trait distributions (symmetric normal or positive skewed) and percentage of epistatic and additive genetic variances (100% epistatic, 50% epistatic and 50% additive, 100% additive). Only additive-by-additive effects were simulated for epistasis. Three replicates were generated per scenario. Estimation of marker effects was performed using 2000 individuals (training). The remaining 500 individuals were used for validation. Accuracy was calculated as the correlation between genomic estimated breeding values and true breeding values. Analyses were performed using Bayesian LASSO (BLASSO) and RQR considering three quantiles (0.15 [RQR0.15 ], 0.50[RQR0.50 ], 0.85[RQR0.85 ]) in R. Results are shown in Table 032 . Overall, accuracies of genomic prediction for the normal symmetric trait were variable. There was no relationship between RQR quantiles and accuracies of genomic prediction. In general, accuracies of genomic prediction decreased as the proportion of epistatic variance increased. The highest accuracies of genomic prediction were 0.15 (BLASSO), 0.17 (BLASSO), and 0.20 (RQR0.15 ) for the proportions of epistatic variance of 100%, 50%, and 0%, respectively. For the positively skewed trait, the greatest accuracies were obtained for RQR0.15, with 0.16, 0.26, and 0.27, followed by RQR0.50, with 0.12, 0.18, and 0.21 for the proportions of epistatic variance of 100%, 50%, and 0%, respectively. Accuracies for RQR0.15 were 77%, 53%, and 50% greater than those obtained using BLASSO. For RQR, accuracies decreased as quantiles increased. Within each method, accuracies were similar for proportions of epistatic variances of 50% and 0%. In conclusion, for the symmetric normal trait, BLASSO had, overall, slightly greater accuracies than for RQR. In contrast, RQR presented greater accuracies of genomic prediction compared to BLASSO when quantiles 0.15 and 0.50 were used for the trait with positive skewness. These results suggest that improved accuracy of genomic prediction for skewed traits can be obtained using RQR. :